PERANCANGAN APLIKASI POINT OF SALE BERBASIS WEB PADA BELIG COFFE MENGGUNAKAN EXTREME PROGRAMMING - Tomy Rizmawan; Daffa Satria Maulana; Bara Pentium Alarsy; Roeslan Djulatov (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
In this era, technology is increasingly sophisticated and modern. Everyone is required to be fast and accurate in working, in the world of working machines or technology are growing, as well as the cashier transaction system at the BATU BELIG COFFE Shop, currently the shop does not have a computerized system. So that in making receipt numbers or receipts using a manual system, namely by handwriting, this can cause the number to be the same or double. Also on the creation of a report each incoming receipt is stacked on a folder. This can also cause the receipt to be lost, tucked away or damaged. In the study, the title "Making a WEB-Based POS (Point Of Sales) Application Using the EXTREME PROGRAMMING method at Kedai Batu Belig Coffee" which aims to make it easier to make transaction numbers and sales reports. The method used is by conducting direct research at the Batu Belig Tavern then analyzing the running system and continuing with the application design and continuing the implementation stage. The result of the research is a cashier application that makes it easier for a cashier to make transactions easier and also to make it easier for sales reports such as receipts have been systemized in their numbering and sales reports are stored in a database and can be printed or printed.